Synthesis of some New 3-Substituted Heterocyclic Compounds Containing Bridgehead Nitrogen from 2-Amino Pyridine with Study Their Biological Activity - Al-Lami, Naeemah; Mahmoud, Ahmad Shaker (Al-Nahrain Journal of Science, 2018)
New series of 3-substituted heterocyclic compounds containing bridge head nitrogen were synthesized through multi-step reactions. In order to prepare the starting 2-substituted heterocyclic compounds of pyridine, a known procedure was used by condensation of 2-amino pyridine with (4-bromo phenacyl bromide). Carbaldehyde group was introduced at position-3 of prepared 2-substituted imidazo / pyridine rings by Vilsmeier-Haack reaction. 3-Carbaldehyde derivatives underwent Claisen condensation with different aryl ketons to give unsaturated ketones of these derivatives, which on cyclization with urea and thiourea afforded 3-cyclic oxopyrimidines and thiopyrimidines derivatives of imidazo / pyridine rings. In addition, 3-carbaldehyde derivatives was reacted with hydrazine, semicarbazide and hydroxyl amine hydrochloride to yield new hydrazone, semicarbazone and oxime derivatives of imidazo / pyridine rings. All prepared compounds were characterised via FT-IR spectroscopy, some of them were characterised by 1H-NMR spectroscopy. These new 3-subistituted derivatives of imidazo /pyridine rings were tested in different species bacterial and fungi. Some of tested compounds showed strong activity while the other showed moderate against. Interestingly, All these new prepared compounds showed high activity against fungi.